Soccer Versus Jihad: A Draw. (August 2016) - Dorsey, James M.
Stadia have reemerged as a preferred jihadist target. The Islamic State (IS) targeted a friendly soccer match between France and Germany in its November 2015 attacks in Paris. (Martinez, 2015) German police said days later that they had foiled a plot against a stadium in the German city of Hannover barely an hour before the German national team was scheduled to play. Similarly, Belgium cancelled a friendly soccer match against Spain (Ryan, 2015). The list of targeted stadia is long. It dates back to an Al-Qaeda plan to strike against the 1998 World Cup and includes sporting grounds in among others Iraq and Nigeria. The targeting of stadia spotlights jihadists' often convoluted relationship to soccer. Many jihadists see soccer as an infidel invention designed to distract the faithful from fulfilling their religious obligations. Yet others are soccer fans or former, failed or disaffected players who see the sport as an effective recruitment and bonding tool. Men like Osama Bin Laden, Hamas' Ismail Haniyeh, and Hezbollah's Hassan Nasrallah base their advocacy of the utility of soccer on those Salafi and mainstream Islamic scholars who argue that the Prophet Mohammed advocated physical exercise to maintain a healthy body as opposed to more militant students of Islam who at best seek to rewrite the rules of the game to Islamicize it, if not outright ban the sport. Self-declared IS Caliph Abu Bakr al-Baghdadi embodies the jihadists' double-edged attitude toward soccer. A passionate player in his pre-IS days (McCant, 2015) Al-Baghdadi's IS and its affiliates take credit for scores of attacks on stadia. A successful attack on a major soccer match in Europe would go a long way to achieve IS's goals of polarizing communities, exacerbating social tensions, and driving the marginalized further into the margins. In targeting the sport and stadia, jihadists focus on the world's most popular form of popular culture and the one fixture that evokes the kind of deep-seated emotion capable of rivalling passions associated with religion and sectarianism. Yet the relationship between militant Islam and soccer is one that has barely been researched by scholars in multiple disciplines, including Islamic, Middle Eastern, and sports studies. This article constitutes a first stab at trying to fill the gap.